WOMEN’S EXPANSION IN REGIONAL HEAD ELECTIONS IN MEDAN CITY 2020 (CASE STUDY ON THE AKHYAR-SALMAN COUPLE) - Arfan, Rocky; Azzahra, Dinda; Suryanef, Suryanef; Rafni, Al (Universitas Padjadjaran, 2023)
The role of women as political elites is increasingly important, which makes gender inequality widespread. This study examines the expansion, role, and contribution of DPD women of the Partai Keadilan Sejahtera (PKS) in the 2020 Medan City regional head elections with a case study on the Akhyar-Salman couple. Qualitative research was conducted by collecting data on the role of female PKS party members and leaders in winning the Akhyar-Salman pair through in-depth interviews with research subjects. sample determination using a purposive sampling technique. All data were processed descriptively. The results showed that the expansion of women in improving the quality and quantity of regional elections in Medan City is significant; this is indicated by the contribution of women’s political elites in mobilizing the implementation of campaigns in the community and attracting public interest from upstream to downstream to introduce the Akhyar-Salman couple. Women’s political elites have functions and responsibilities in winning candidate pairs through door-to-door campaigns to each household, creating work programs that attract women to join, such as carrying out women’s recitation (dakwah), helping communities affected by disasters, and carrying out approaches to the ulama. In addition, the most prominent expansion of women lies in the gender equality program and equal access to information, which have the most decisive influence on the campaign process. The work program launched by the mayoral and deputy candidate pairs is the result of preliminary studies of the community and data collection by the DPD PKS women’s political elites. Finally, the Japuan program (women’s network) indicates that voter accommodation and navigation can be appropriately managed by disseminating information related to candidate pairs by political elites from the PKS party.